1997
DOI: 10.1121/1.417972
|View full text |Cite
|
Sign up to set email alerts
|

Toward articulatory-acoustic models for liquid approximants based on MRI and EPG data. Part II. The rhotics

Abstract: Magnetic resonance images of the vocal tract during sustained production of [symbol: see text] by four native American English talkers are employed for measuring vocal-tract dimensions and for morphological analysis of the 3D vocal tract and tongue shapes. Electropalatography contact profiles are used for studying inter- and intra-talker variabilities. The vocal tract during the production of [symbol: see text] appears to be characterized by three cavities due to the presence of two supraglottal constrictions:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 3 publications
3
76
1
Order By: Relevance
“…The distinctive 'dip' or lowered F3 values for the rhotacized vowel is likely to be the result of similar articulatory configurations that are typically reported for /‰/ (e.g. Alwan et al, 1997;Espy-Wilson et al, 2000) and replicates previously reported speaker sex differences in adults for the formant frequency values of /‰/ (Westbury et al, 1998).…”
Section: B Fundamental Frequency and Formant Frequency Patterns Usinsupporting
confidence: 61%
See 2 more Smart Citations
“…The distinctive 'dip' or lowered F3 values for the rhotacized vowel is likely to be the result of similar articulatory configurations that are typically reported for /‰/ (e.g. Alwan et al, 1997;Espy-Wilson et al, 2000) and replicates previously reported speaker sex differences in adults for the formant frequency values of /‰/ (Westbury et al, 1998).…”
Section: B Fundamental Frequency and Formant Frequency Patterns Usinsupporting
confidence: 61%
“…Alwan et al, 1997;Espy-Wilson et al, 1997, and the creation of a sublingual cavity anterior between the palatal and lip constriction (e.g. Espy-Wilson and Boyce, 1999).…”
Section: B Fundamental Frequency and Formant Frequency Patterns Usinmentioning
confidence: 99%
See 1 more Smart Citation
“…Speakers employ a wide variety of articulations that result in lowered F 3 [e.g. [8][9][10][11]. Variation in articulation strategies extends even to Japanese English speakers, as Masaki et al [12] discovered in an MRI study, finding 4 distinct strategies for differentiating /ô/ and /l/ employed by both native English speakers and Japanese learners.…”
Section: Variable Pronunciations Of /ô/ and /L/mentioning
confidence: 99%
“…Engwall [7] built polygon mesh data of the teeth and palate using a dental cast for the same purpose. Narayanan et al [8,9] and Alwan et al [10] measured casts using calipers, and sliced dental impressions to trace the outlines of the slices. This method was also adopted by Espy-Wilson et al [11].…”
Section: Introductionmentioning
confidence: 99%